Pengembangan Media Pembelajaran Matematika berbasis QR Code untuk Kemampuan Berpikir Geometris Siswa Kelas IV SD - Excel Juni Vawanda; Melva Zainil (Universitas Negeri Padang, 2022)
The purpose of this study was to design a mathematics learning media based on qr code to find out the level of geometric thinking of grade IV elementary school students. This research belongs to Research and Development (R&D with ADDIE models, namely Analysis, Design, Development, Implementation, Implementation, and Evaluation). Learning media that have been developed will be assessed and validated by experts who are competent in their fields The instrument used in this study was a questionnaire in the form of teacher responses and student responses to the qr code-based mathematics learning media Results: 1) The author has produced a qr code-based mathematics learning media on the circumferential material and building area flat for grade IV SD / MI students, 2) Expert assessment in material validation, media validation, and language validation which gets a percentage of 96% at highly valid intervals, 3) responses of grade IV SD / MI students on the practicality of the media based on mathematics based learning qr code obtained an evaluation percentage of 87%. This value is at a very, very practical interval.